MULTIPLE INTELLIGENCES PROFILE OF EFL STUDENTS AT SMP MUHAMMADIYAH 15 SURABAYA - Rahmawati, Laila Eka; Mayasari, Linda; Wijaya, Sulton Dedi (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2020)
This research analyzes the multiple intelligences in English Foreign Language (EFL), especially in 8A grade students. It identifies the multiple intelligences profile based on the frequency of multiple intelligence (MI) types, students' high and low scores. This research uses a descriptive quantitative design. The subject of this research was 8A grade students in SMP Muhammadiyah 15 Surabaya. The research instruments were the Multiple Intelligences questionnaire, IQ results, and documentation of English mid-test scores in the second semester. From analysis and discussion, it was found that this class's IQ score average is 86, and the most dominant intelligence type is musical. For the five highest score students,' there were four types of intelligence that they had. They were interpersonal, naturalist, logical-mathematical, and musical. Meanwhile, five low English achievers had four types of multiple intelligence: musical, interpersonal, naturalist, and visual-spatial. In conclusion, the class has diversity in multiple intelligence. Multiple Intelligence types cannot refer to a certain group, in this case, groups based on their English score, because some MI types can be found in the high and low English achiever groups.